PENGARUH GREEN ACCOUNTING DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN SEKTOR BASIC MATERIALS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2023 - Talytha Anastasya; Santi Susanti; Ati Sumiati (CV. Denasya Smart Publisher, 2025)
This study aims to examine the effect of Green Accounting, Corporate Social Responsibility (CSR) and Company Size as moderating variables on Profitability. The research method used in this research is quantitative method. Data collection techniques are carried out by documentation techniques. The population used in this study is the Basic Materials Sector Company listed on the Indonesia Stock Exchange in 2023. The sampling technique used was purposive sampling with the final sample being 53 sample companies. Data obtained by collecting annual financial report data and sustainability reports of Basic Materials Sector Companies on the website of each company. The data analysis technique used is simple regression analysis and Moderated Regression Analysis (MRA) which has previously passed the classical assumption test and hypothesis testing using the help of SPSS software version 26 for windows. The results showed that Green Accounting and Corporate Social Responsibility (CSR) had no effect and were not significant to Profitability, and company size could not moderate the effect of Green Accounting on Profitability and company size could not moderate the effect of Corporate Social Responsibility (CSR) significantly on Profitability in basic materials companies.